Decreased cardiac parasympathetic activity in chronic heart failure and its relation to left ventricular function. Issue 6 (June 1992) - Nolan, J; Flapan, A D; Capewell, S; MacDonald, T M; Neilson, J M; Ewing, D J
Abstract : BACKGROUND–Activation of the sympathetic nervous system has been extensively studied in patients with chronic heart failure, but the parasympathetic nervous system has received relatively little attention. The objective in this study was to investigate cardiac parasympathetic activity in chronic heart failure and to explore its relation to left ventricular function. METHODS–Heart rate variability was measured from 24 hour ambulatory electrocardiograms by counting the number of times each RR interval exceeded the preceding RR interval by more than 50 ms (counts). This method provided a sensitive index of cardiac parasympathetic activity. RESULTS–Mean (range) of counts were: waking 48 (1-275)/h, sleeping 62 (0-360)/h, and total 1310 (31-7278)/24 h. These were lower than expected, and in 26 (60%) of the 43 patients counts fell below the lower 95% confidence intervals (95% CI) for RR counts in normal subjects. A significant correlation between total 24 hour RR counts and left ventricular ejection fraction was present (r = 0.49, p less than 0.05). CONCLUSIONS–These results indicate that most patients with chronic heart failure have reduced heart rate variability and therefore reduced cardiac parasympathetic activity. The degree of parasympathetic dysfunction is related to the severity of left ventricular dysfunction. This may be relevant to the high incidence of ventricular arrhythmias and poor prognosis of patients with chronic heart failure.